Multifunctional DNA Nanoflower Applied for High Specific Photodynamic Cancer Therapy In Vivo - Zheng, Hao; Feng, Xue‐Nan; Jin, Xiang‐Wan‐Er; Dai, Zhi‐Qi; Lu, Sha; Cui, Yun‐Xi; Kong, De‐Ming (Chembiochem : a European journal of chemical biology, 2024)
Photodynamic therapy (PDT) is a newly emerged strategy for disease treatment. One challenge of the application of PDT drugs is the side‐effect caused by the non‐specificity of the photosensitive molecules. Most of the photosensitizers may invade not only the pathogenic cells but also the normal cells. In recent, people tried to use special cargoes to deliver the drugs into target cells. DNA nanoflowers (NFs) are a kind of newly‐emerged nanomaterial which constructed through DNA rolling cycle amplification (RCA) reaction. It is reported that the DNA NFs were suitable materials which have been widely applied as nanocargos for drug delivery in cancer chemotherapeutic treatment. In this paper, we have introduced a new multifunctional DNA NF which could be prepared through an one‐pot RCA reaction. This proposed DNA NF contained a versatile AS1411 G‐quadruplex moiety, which plays key roles not only for specific recognition of cancer cells but also for near‐infrared ray based photodynamic therapy when conjugating with a special porphyrin molecule. We demonstrated that the DNA NF showed good selectivity toward cancer cells, leading to highly efficient photo‐induced cytotoxicity. Moreover, the in vivo experiment results suggested this DNA NF is a promising nanomaterial for clinical PDT. A kind of DNA based nanostructure was constructed. This DNA nanoflower structure can targeted deliver photosensitizer molecules into cancer cells, thus can be applied for specific photodynamic therapy for tumor treatment.